(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Statesocial capitalis critical to ensurethe national securitystateandcountry’s prestigein the international arena. Social capitalarises mainlyfromthe economic power ofthe state,which can easilybe translated intomilitary power, and thus ensurean adequate levelof national security.Importance ofsize and qualityof social capitalresults from the factthatit alsoaffectsthe rapidsocio-economic developmentas well as thequality of lifein the country